Measuring the Impact of Ease of Use, Usefulness, Attitude, and Enjoyment toward Intention to Play PUBG Mobile - Dewi, Berlinda Devi Liliyana (Journal of Business, Management, and Social Studies, 2022)
The impact of ease of use, usefulness, attitude, and enjoyment toward intention to play PUBG Mobile as it relates to Indonesians, is explicitly examined in this study’s examination of the mobile gaming era because of the pandemic. This paper investigates the factors that influence an individual’s intention to play PUBG Mobile and the outcome of those factors towards its individuals, as well as the effects of knowledge about gaming behavior to its users. The study’s recommendations are to increase the intention to play mobile games so that the need for enjoyable aspects and the need for outside assistance become more apparent. Through an online survey, 223 individuals provided information for this study. The survey asked for responses from people who had played a mobile game, particularly Player Unknown Battle Ground Mobile version (PUBGM), millennials or members of Generation Z having enrolled in college and who previously had resided in Indonesia, had at least played PUBG Mobile in the past, and had played it more than one year. In this work, statistical analysis is carried out. The outcome demonstrates that perceived ease of use, usefulness, attitude, and perceived enjoyment have an impact toward Intention to play PUBG Mobile. This study closes a gap in the literature by concentrating on the behavioral intention to play PUBG through the playful-consumption experiences of a well-known online multiplayer game.